Purification Effect of Water Eutrophication Using the Mosaic System of Submerged–Emerged Plants and Growth Response - Baoliang Chang; Yingchun Xu; Ze Zhang; Xiaowen Wang; Qijiang Jin; Yanjie Wang (Plants, 2024)
Aquatic plants play a crucial role in the sustainable management of eutrophic water bodies, serving as a valuable tool for water purification. However, the effectiveness of using aquatic plants for improving water quality is influenced by landscape considerations. In practical applications, challenges arise concerning low purification efficiency and compromised aesthetic appeal when utilizing plants for water purification. To address these issues, this study aimed to examine the impact of aquatic plants on the purification of simulated landscape water bodies, specifically focusing on the effectiveness of the mosaic system of submerged–emerged plants in remediating eutrophic water bodies. Our findings indicated that individual aquatic plants exhibited limited efficacy in pollutant (total nitrogen, total phosphorus, ammonia nitrogen, and chemical oxygen demand) removal. However, when combined in appropriate proportions, submerged plants could enhance species growth and improve the purification efficiency of polluted water bodies. Notably, the mosaic system of submerged–emerged plants neither significantly promoted nor inhibited the growth of each other, but it effectively removed pollutants from the simulated water bodies and inhibited turbidity increase. The comprehensive evaluation ranked the purification capacity as Canna indica-submerged plants combination (C + S) > Thalia dealbata-submerged plants combination (T + S) > Iris pseudacorus-submerged plants combination (I + S) > Lythrum salicaria-submerged plants combination (L + S). Both C + S and T + S configurations effectively mitigated the rise of water turbidity and offered appealing landscape benefits, making them viable options for practical applications in urban landscape water bodies. Our study highlights that a submerged–emerged mosaic combination is a means of water purification that combines landscape aesthetics and purification efficiency.